Quality of Food Souvenirs to Support Agribusiness and its Effect on Satisfaction and Loyalty - Levyda Levyda; Giyatmi Giyatmi; Kania Ratnasari (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2023)
Food souvenirs have a strategic role in supporting agribusiness. Although it has an important role, there is no agreement on the factors that affect the quality of food souvenirs. This study aims to develop a model for measuring the quality of food souvenirs and testing the influence of food souvenir quality on tourist satisfaction and loyalty. In this study, the quality of food souvenirs is a multi-dimensional construct and second order. The sample of this study was 339 people selected by purposive sampling.The data is processed using SEM PLS. The quality of food souvenirs is reflected in the appearance, authenticity, packaging, health benefits, price, and taste. Taste, price, and appearance have the greatest role to play in quality. The quality of food souvenirs effect on tourist satisfaction and tourist satisfaction effect on loyalty. Food souvenir manufacturers should improve those attributes especially the taste, price, and appearance of food souvenirs.